The Relationship Between the Use of Headscarves (Hijab) and Hair Loss (Effluvium) Prevalence in Medical Students - Febrina Dewi Pratiwi Lingga; Tiara Dwi Vania (Faculty of Medicine, Universitas Airlangga, 2026)
Background: In general, female students wear the headscarves for extended periods during daily activities. Prolonged headscarf use keeps the hair covered and pulled, creating a more humid environment with reduced oxygen flow and retained heat around the scalp. As a result, scalp complaints such as limp hair, dandruff, and hair loss (effluvium) are commonly reported among headscarf users. Both internal and external factors can cause hair loss (effluvium). To determine whether there is a relationship between headscarf use and hair loss (effluvium) in medical students of the University of Muhammadiyah North Sumatra class of 2020. Methods: This study is an analytical observational study with univariate and bivariate analysis, using the cross-sectional method. Data collection used a questionnaire. The number of samples in this study was 62. The sample in this study were students of the Faculty of Medicine, Muhammadiyah University of North Sumatra, class of 2020. Results: The bivariate analysis yielded a p-value of ​​0.740 (p>0.05). with the number of headscarf users who are proper and experience hair loss and do not experience hair loss respectively 25 people (49.9%) vs 26 people (51%). While in the group of headscarf users who are improper, those who experience hair loss and those who do not are respectively 6 people (54.5%) vs 5 people (45.5%). Conclusion: No significant association was found between headscarf use and hair loss.